FRI0268 Multifunctional Flow Cytometry Analysis of CD4+ T Cells as an Immune Biomarker for Latent Tuberculosis Status in Patients Treated with TNF Antagonists. (10th June 2014) - Scrivo, R.; Sauzullo, I.; Mengoni, F.; Ermocida, A.; Vullo, V.; Mastroianni, C.M.; Valesini, G.
Abstract : Background: No strategy has yet proved successful in monitoring tuberculosis (TB) infection during treatment with TNF antagonists. Even the new interferon-gamma (IFN-γ) release assays (IGRAs) produce dynamic changes in IFN-γ plasma levels with little correlation to clinical change. Recent studies show that multifunctional analysis of CD4 + T cells producing IFN-γ, IL-2, and TNF in response to M. tuberculosis -specific antigens may discriminate between active and latent TB infection (LTBI) and be superior to IGRAs in terms of TB detection. Objectives: To investigate the performance of multifunctional CD4 + T cells by intracellular cytokine flow cytometry assay in subjects with chronic inflammatory rheumatic diseases during long-term anti-TNF treatment. Methods: Before initiating biological therapy, patients underwent TB screening, also including QuantiFERON-TB Gold In-Tube (QFT-GIT), one of the IGRAs currently available. Patients with evidence of TB infection based on any of QFT-GIT, tuberculin skin test, chest radiograph results or other risk factors were considered affected by LTBI after excluding active TB. These subjects received a 9 month-course of isoniazid. QFT-GIT was serially repeated during biological therapy; after 36 months multifunctional analysis was also performed. Patients were classified into 3 groups based on their TB status before the onset of biological treatment and on IFN-γ level fluctuations evaluated by QFT-GIT during the follow-up: 12 patients with LTBI who showed IFN-γ level fluctuations; 11 patients with no evidence of LTBI at baseline showing IFN-γ level fluctuations and 10 patients with no evidence of LTBI at baseline and persistently negative IFN-γ levels. Results: No patient developed active TB during treatment with TNF antagonists. In LTBI subjects we observed a higher frequency of IFN-γ+ IL-2+ TNF+ CD4 + T cells compared to LTBI-negative patients showing IFN-γ level fluctuations (p=0.015), but no difference with respect to patients with no LTBI and persistently negative IFN-γ levels. The frequency of IFN-γ+ IL-2+ CD4 + T cells was significantly higher in LTBI patients compared to the other 2 groups of patients with no evidence of LTBI at baseline (p=0.006). Patients with no LTBI and persistently negative IFN-γ levels showed similar proportions of cells producing IFN-γ alone, IL-2 alone, and IL-2 in combination with TNF in response to M. tuberculosis -specific antigens. Conclusions: This is the first study evaluating multifunctional analysis of CD4 + T cells in patients treated with TNF antagonists, and suggests that it could be useful for ruling-out TB infection in patients classified at screening as LTBI-negative but who showed IGRA fluctuations under long-term TNF antagonist treatment. Despite LTBI patients were treated with isoniazid, their CD4 + T cells were found to produce multiple cytokines, unlike patients with no LTBI. Hence, multifunctional analysis may be a useful means of clarifying TB status when IFN-γ levels fluctuate with repeated IGRA testing, even in patients undergoing biological therapy. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2520